2022
DOI: 10.3389/fmed.2022.819670
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Radiomics-Based Prediction of Microvascular Invasion in Hepatocellular Carcinoma

Abstract: BackgroundDue to the high recurrence rate in hepatocellular carcinoma (HCC) after resection, preoperative prognostic prediction of HCC is important for appropriate patient management. Exploring and developing preoperative diagnostic methods has great clinical value in treating patients with HCC. This study sought to develop and evaluate a novel combined clinical predictive model based on standard triphasic computed tomography (CT) to discriminate microvascular invasion (MVI) in hepatocellular carcinoma (HCC).M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
(42 reference statements)
1
5
0
Order By: Relevance
“…Moreover, this study showed better performance using arterial and equilibrium phase images compared to MR-T2WI and portal venous phase, aligning with the findings of Zhu et al [ 31 ]. However, this study deviates from previous ones[ 32 , 33 ], where some have indicated that radiomic sores of the portal venous phase surpass those of the arterial or equilibrium phases. This could be attributed to selection bias and inclusion criteria.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, this study showed better performance using arterial and equilibrium phase images compared to MR-T2WI and portal venous phase, aligning with the findings of Zhu et al [ 31 ]. However, this study deviates from previous ones[ 32 , 33 ], where some have indicated that radiomic sores of the portal venous phase surpass those of the arterial or equilibrium phases. This could be attributed to selection bias and inclusion criteria.…”
Section: Discussioncontrasting
confidence: 99%
“…Yao et al revealed that tumor size and histological grade are independent factors related to MVI(33), which is in accordance with our data. Notably, to date, there is no consensus on the relationship between tumor quantity and MVI.…”
supporting
confidence: 93%
“…The combined model developed from images of two phases (portal venous and hepatobiliary phase) of gadolinium-ethoxybenzyl-diethylenetriamine-pentaacetic acid (Gd-EOB-DTPA)-enhanced MRI might be used to predict the VEGF level in HCC ( 28 ). Microvascular invasion (MVI) in individuals with HCC can be predicted using models developed from triphasic CT ( 29 ). In pediatric medulloblastoma, the radiomics signature and nomogram performed well in predicting progression-free survival (PFS) ( 30 ).…”
Section: Discussionmentioning
confidence: 99%